2020
DOI: 10.1111/trf.15721
|View full text |Cite
|
Sign up to set email alerts
|

Deaths and complications associated with the management of acute immune thrombotic thrombocytopenic purpura

Abstract: BACKGROUND The introduction of therapeutic plasma exchange (TPE) dramatically decreased mortality in patients with immune thrombotic thrombocytopenic purpura (iTTP). However, there are few modern descriptions of residual causes of death from iTTP and complications associated with TPE. STUDY DESIGN AND METHODS This was a retrospective study in a multi‐institutional cohort of 109 patients with iTTP between 2004 and 2017. Complications of TPE were analyzed in a subset of this cohort (74 patients representing 101 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…The advent of TPE in the 1980s and 1990s transformed TTP from an almost uniformly fatal condition into a treatable disease with an approximately 90% survival rate 2,27 . Accordingly, clinical practice guidelines recommend immediate initiation of TPE in all patients with suspected TTP 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of TPE in the 1980s and 1990s transformed TTP from an almost uniformly fatal condition into a treatable disease with an approximately 90% survival rate 2,27 . Accordingly, clinical practice guidelines recommend immediate initiation of TPE in all patients with suspected TTP 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Insertion of an apheresis catheter carries a risk of bleeding, infection, and thrombosis. Exposure to plasma may result in allergic reactions or transfusion‐related acute lung injury 27,30 . Moreover, in patients without TTP, effective treatments (eg, anti‐complement therapy for atypical hemolytic‐uremic syndrome) may be delayed while TPE is administered.…”
Section: Discussionmentioning
confidence: 99%
“…9 While the introduction of plasmapheresis has dramatically improved survival rates, mortality remains between 7-22% in those who receive standard treatment. [10][11][12] Delayed diagnosis and treatment have been reported to contribute significantly to this mortality rate and to an increased risk of relapse. 10,11 In a small retrospective study examining TTP-related deaths at six institutions, Colling et al reported an association between mortality and a delay in the initiation of plasma exchange for more than 24 hours after presentation, highlighting the urgency for rapid diagnosis and immediate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Delayed diagnosis and treatment have been reported to contribute significantly to this mortality rate and to an increased risk of relapse. 10,11 In a small retrospective study examining TTP-related deaths at six institutions, Colling et al reported an association between mortality and a delay in the initiation of plasma exchange for more than 24 hours after presentation, highlighting the urgency for rapid diagnosis and immediate treatment. 11 However, early diagnosis of iTTP can be challenging, as symptoms are often generalized and overlap with various other forms of thrombotic microangiopathies, and the clinical presentation can vary widely between patients.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, while the complete dataset was characterized by a very high mortality rate (24/134, 17·9%), death itself was not included within the definition of refractoriness, thereby limiting the clinical utility of the AHC score. This is relevant in light of prior work suggesting that early deaths are not uncommon in iTTP, 7 and some patients may die before they are able to meet the definition of refractoriness. Additionally, rituximab (RTX) was used in only a subset of refractory patients (28/55) and it is possible that the AHC score may be less predictive in settings where RTX is used as standard of care.…”
Section: Risk Factor Category Pointsmentioning
confidence: 95%